Back diffusion of manganese during solidification of carbon steels - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
In this study, back diffusion of manganese in solid between secondary arms in the ternary Fe - 1.6 wt % Mn - 0.1, 0.21, 0.4 and 0.75 wt % C alloys was investigated in unidirectionally solidified quenched specimens which solidified in the range of 0.25 K/s to 4.15 K/s cooling rates. Manganese back diffusion in the solid phase during the growth has a large influence on microsegregation when the first solid formed is delta-ferrite. A decrease in Cmin after 0.1 wt % C has been observed because the fraction of delta phase decreases with increasing carbon content. Only a small rise during the growth was found in both 0.4 and 0.8 wt % C steels but there was no difference between them indicating that both solidify as austenite. Secondary dendrite arms grown at the lowest cooling rate (around 0.3 K/s) always disappeared at the end of solidification for all steels. These high increases in Cmin were attributed to the high coarsening, back diffusion and TGZM processes. The Cmin calculations obtained from the secondary dendrite arm coarsening model are in a good agreement with the experimental measurements.
Keywords: microsegregation; back diffusion in solid; dendrite arm coarsening; temperature gradient zone melting (TGZM); carbon steels